Myxoma versus myxoid liposarcoma involving the kidneys. Issue 3 (3rd July 2019) - Findeis, Sarah K.; Salicru, Mauricio N.; Agarwal, Atin
Abstract: Myxoid lesions of the kidney are rare. We present a case of a 74-year-old man who presented with an 8.5 × 8.0 × 6.0 cm left kidney mass that was grossly confined to the kidney and had a gelatinous cut surface. Histology of the tumor showed bland spindle cells in a myxoid stroma with interspersed thin-walled vessels. The tumor was negative for smooth muscle actin, desmin, CD34 (highlighted vessels), S100, and HMB-45 by immunohistochemistry. There was focal, nonspecific staining of MDM2 and CDK4. The lesion appeared more vascular than would be expected for a classic myxoma and, therefore, fluorescence in situ hybridization was performed for the 12q13 ( DDIT3 or CHOP ) rearrangement to rule out myxoid liposarcoma and the result was negative for a rearrangement. This case highlights the difficulty of delineating a primary myxoma of the kidney from a well-differentiated myxoid liposarcoma.